Genetic Factors, Obesity, Age, and Lifestyle on the Prevalence of Diabetes Mellitus - Miranti Ika Indah Prameswari; Eka Wilda Faida (PT Bukuloka Literasi Bangsa, 2025)
Diabetes mellitus (DM) is a degenerative disease that continues to increase in prevalence throughout the world, with most cases classified as type 2 diabetes mellitus. Globally, the number of diabetes mellitus sufferers in 2021 is estimated at 537 million adults aged 20-79 years and is estimated to be 643 million people in 2030. This study aims to determine the relationship between genetics, obesity, age, and lifestyle with Diabetes mellitus patients at Bhakti Dharma Husada Hospital. The research design used an analytical survey with a cross-sectional approach. The population consisted of patients with type 2 Diabetes mellitus cases in March 2024, totaling 7,805 patients, with a sample size of 100 respondents. The sampling method used was accidental sampling, and data was collected using a questionnaire. Data analysis used the chi-square test with a confidence level of 95%. Of the 100 respondents, 70 people (70%) suffered from type 2 diabetes mellitus. Based on the results of statistical tests, it was found that there was no relationship between genetic factors and the incidence of diabetes (p-value = 0.826), there was no relationship between obesity factors and the incidence of diabetes (p-value = 0.406), there was an age factor with the incidence of diabetes (p-value = 0.001), and there was no relationship between lifestyle factors and physical activity factors (p-value = 0.787); cigarette factor components (p-value = 0.104); alcoholic beverage factor components (p-value = 0.824); and diet factor components (p-value = 0.617). Age factors need to be considered in carrying out diabetes care. Keywords: Genetics, Obesity, Lifestyle, Prevalence Diabetes Mellitus